Introduction (Scottish Historical and Archaeological Internet Reports, 2005)
A brief description of the study area is provided along with the circumstances of the work. The name Arisaig is used to refer to coastal land between Loch nan Uamh (Borrodale) in the south and the River Morar in the north.